Anticancer Studies Of Koetjapic Acid Purified From Sandoricum Koetjape MERR - Nassar, Zeyad D. (2011)
Colorectal cancer which involves the colon, rectum and the anal canal is the third most common malignancy worldwide. The disease is characterized by extensive angiogenesis and perturbation of a variety of oncogenes and tumor suppressor genes including, p53, Wnt, hypoxia, NF-кB, Notch, MAP kinase. Targeting one or more of these pathways increases the selectivity of the chemotherapeutic agents as these pathways are important for cancer cells growth and proliferation. Koetjapic acid is a naturally occurring seco-A-ring oleanene triterpene present in the Sandoricum koetjape species that grows in Malaysia and the Southeast Asian region.